The new rules of retail : competing in the world's toughest marketplace - Lewis, Robin, 1940-; Dart, Michael (New York, NY : Palgrave MacMillan, 2010)
'Unprecedented consumer power, enabled by technology and globalization is driving a revolutionary transformation that will lead to the demise of retail as we know it. The authors provide a unique and essential view of the future of the industry, arguing that a new business model is necessary in these new times, one based on: Preemptive, precise and perpetual distribution; A neurological customer connection; and total control of the value chain. Some of the authors' key insights and predictions include: * The collapse of the traditional retail/wholesale business model: The more enlightened retailers and wholesalers understand they must own and control the creation, distribution and presentation of their value, directly to the consumer. * Internet retailers such as Amazon, must ultimately open bricks and mortar stores: In an over-competed marketplace, preemptive distribution of value to precisely where and how the consumer wants it is vital, meaning that retailers and wholesalers must utilize all available distribution platforms, as well as create new distribution ideas. * Successful control of the total value chain is the key driver of economic success: Control does not necessarily mean ownership, as in complete vertical integration. Rather, it means that one must gain dominant control over all its functions as companies like Wal-Mart and Ralph Lauren, who don't own, but certainly control, their total value chains, demonstrate. * The imperative to control the value chain will favor those who own production: An increasing number of U.S. brands, wholesalers and retailers, will be acquired by Chinese manufacturers and other emerging countries who can produce consumer goods at a low cost.'--
Includes bibliographical references and index.
Keywords: Retail trade; Retail trade -- Management; Retail trade -- Technological innovations; Wholesale trade; Consumer satisfaction